Association between phenols and thyroid hormones: The role of iodothyronine deiodinase genes. (15th October 2022) - Sarzo, Blanca; Abumallouh, Reem; Marín, Natalia; Llop, Sabrina; Beneito, Andrea; Lopez-Flores, Inmaculada; Ferrero, Nerea; Sakhi, Amrit Kaur; Ballester, Ferran; Lopez-Espinosa, Maria-Jose
Abstract: Previous literature on prenatal phenol exposure and thyroid hormone (TH) alteration is conflicting, and the possible mechanisms of action involved remain unclear. We aimed to examine the association between prenatal phenol exposure and levels of maternal and neonatal THs, as well as the possible role of iodothyronine deiodinase ( DIO ) gene polymorphisms in this relation. We studied 387 Spanish mother–neonate pairs with measurements of maternal phenols, total triiodothyronine (TT3) and free thyroxine (FT4), maternal and neonatal thyroid-stimulating hormone (TSH), and maternal genotypes for single nucleotide polymorphisms in the DIO1 (rs2235544) and DIO2 (rs12885300) genes. We implemented multivariate linear and weighted quantile sum (WQS) regressions to examine the association between phenols and THs (including sex-stratified models for neonatal TSH) and investigated effect modification of genotypes in the maternal phenol-TH associations. In single exposure models, we found negative associations between maternal triclosan (TCS) and neonatal TSH (% change [95%CI]: −2.95 [-5.70, -0.11], per twofold phenol increase) – stronger for girls – and less clearly for maternal ethylparaben (EPB) and TSH (−2.27 [-4.55, 0.07]). In phenol mixture models, we found no association with THs. In the genetic interaction models, we found some evidence of effect modification of DIO gene polymorphisms with stronger negative associations between methylparaben (MPB), propylparaben (PPB), butylparaben (BPB) and TT3 as well as bisphenol A (BPA) and FT4 for DIO1 (rs2235544)-CC. Stronger inverse associations for genotypes DIO2 (rs12885300)-CC and DIO2 (rs12885300)-CT and positive ones for DIO2 (rs12885300)-TT were also reported for BPA and FT4. In conclusion, we found some evidence of an association between phenols and TSH during pregnancy and at birth in single exposure models, the latter being stronger for girls. Since no association was observed between maternal levels of phenols and TT3 or FT4, the possible role of the genetic background in these associations warrants further investigation. Graphical abstract: Image 1 Highlights: Association between some phenols and TSH during pregnancy and at birth. Possible sex modification of the association between maternal TCS and neonatal TSH. First study in humans on the possible role of DIO gene polymorphisms on how phenols might target THs. Some evidence of effect modification of DIO gene polymorphisms in the phenol-TH associations.